The Application of Digital Marketing to UMKM Roso Kangen Pakde - Fresha Febri Yunus; Ronny Firdiansyah Arief (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
UMKM Roso Kangen Pakde is a business engaged in culinary food. This Roso Kangen Pakde culinary business provides many menus such as mie ayam, bakso, ayam penyet, pecel lele and many others. The purpose of implementing digital marketing for the Roso Kangen Pakde business is so that this business can be better known by the people of Batam. Create a good business image so that consumers are interested in visiting and can increase sales turnover. This program collects data using observation, documentation and interview methods. Based on the results of implementing digital marketing promotions, Roso Kangen Pakde business using Instagram and Mailchimp is able to provide the latest information to business owners about knowledge of how to use social media as a good digital promotion tool. The implementation of Instagram for the Roso Kangen Pakde business as a promotional tool is useful for providing information to consumers such as food menus along with photos of food, whatsapp numbers that can be contacted and google maps links which make it easier for consumers to find business locations.